"The influence of emotional intelligence the oral proficiency of english as a second language in the students of the last semester of the english teaching career at UDELAS" - González Alvarez, Yessy Yamileth (David, Panamá : UDELAS, 2011)
This work focuses on the positive relationship between the emotional intelligence and the learning of english as a second language . The emotional intelligence plays a key role within the learning process and it must be considered as a critical factor because it reduces anxiety and inhibitions; and the most important, it enhances learners motivation and self-esteem.
GENERAL INDEX Thought Dedication Acknoledgement General index Chart index Graphic index Introduction CHAPTER 1: RESEARCH PROBLEM CHAPTER 2: THEORETICAL FRAMEWORK 2.1. Hisotircal background 2.2. Theory of the multiple intelligences 2.2.1. Linguistic intelligence 2.2.2. The logical-mathematical intelligence 2.2.3. Spatial intelligence 2.2.4. Musical intelligence 2.2.5. Kinesthic intelligence 2.2.6. Naturalistic intelligence 2.2.7. Interpersonal intelligence 2.2.8. Intrapersonal intelligence 2.3. History of the emotional intelligence concept 2.4. What is emotional intelligence 2.5. Branches of the emotional intelligence 2.5.1. Self-awareness 2.5.2. Emotional control 2.5.3. Self -motivation 2.5.4. Empathy 2.5.5. Social skills 2.6. Teaching techniques and methods related to emotional intelligence 2.6.1. Teachers' importance in the edevelopment of emotional intelligence 2.7. Importance of the emotional intelligence 2.7.1. Importance of the emotional intelligence at school 2.7.2. Importance of the emotional intelligence in the professional life 2.7.3. Importance in the development of emotional intelligence in relation with the learning of a second language like english CHAPTER 3: METHODOLOGICAL FRAMEWORK CHAPTER 4: ANALYSIS OF THE RESULTS CHAPTER 5: PROPOSAL Conclusion Recommendation Bibliography Annex
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; SOCIAL AND SPECIAL EDUCATION FACULTY; BACHELOR DEGREE IN ENGLISH TEACHING; LICENCIATURA DE DOCENCIA EN INGLÉS